(untitled) (Journal of Interdisciplinary Insights, 2025)
Focusing on AIGC-empowered dissemination of fine traditional Chinese culture, this study further explores the new logic of AI-Generated Content (AIGC) in the digital inheritance of traditional culture by sorting out the application scenarios and actual effects of AI-generated content in the CCTV Spring Festival Gala and Henan Spring Festival Gala in recent years. The paper summarizes the specific characteristics of AIGC-generated content themed on fine traditional Chinese culture in specific Spring Festival Gala programs, such as scenario construction, symbol transfer, image shaping, and visual extension. The study proposes that to achieve the dynamic balance between technical rationality and humanistic value, and provide optimized paths for the creative transformation and innovative development of fine traditional Chinese culture, measures should be taken through paths including constructing a cross-media narrative space, improving the cultural governance policy system, and bridging the digital-intelligent technology divide.